Nursery-reared coral outplanting success in an upwelling-influenced area in Costa Rica - Fabregat-Malé, Sònia (2023)
Introduction: Environmental and intrinsic factors such as seawater temperature, salinity, nutrient concentration, upwelling, species, and life history can influence coral outplant survival and growth, and in consequence, the effectiveness of restoration. Thus, it is key to understand how these factors can shape coral outplant performance to ensure the long-term success of a restoration program.  Objective: To establish the survival and growth rate of outplanted coral nursery-reared colonies of branching Pocillopora spp. and massive corals Pavona gigantea, Pavona clavus, and Porites lobata in Bahía Culebra, North Pacific of Costa Rica, and to determine whether the site of origin of the coral fragment and the presence of seasonal upwelling affected the growth of Pocillopora outplants.  Methods: From September 2020 to September 2021, we monitored the survival, health, and growth of 30 Pocillopora spp. colonies from six donor sites, and 31 fragments of massive species (P. gigantea [n = 18], P. clavus [n = 8], P. lobata [n = 5]) that were outplanted to a degraded reef. We recorded in situ seawater temperature, salinity, and nutrient concentration.  Results: By the end of the year, 100 % of the Pocillopora spp. outplants survived. Survival was 71.4 % for P. clavus, 47.5 % for P. gigantea, and 20 % for P. lobata. Coral tissue loss and predation marks were observed at least once in 71 % of massive outplants. Pocillopora spp. colonies increased their initial area in 333.1 %, at a rate of 9.98 ± 1.69 cm yr-1. The site of origin of the outplant influenced growth rate, but not the presence of seasonal upwelling. Massive species fragments grew at a rate of 1.35 ± 0.24 cm yr-1 for P. clavus, 1.48 ± 0.21 cm yr-1 for P. gigantea, and 0.61 cm yr-1 for P. lobata, with no differences among them.  Conclusions: Environmental conditions at site level allow for high survival and growth of Pocillopora spp. outplants, previously considered as sensitive to stressors, and point towards acclimation to seasonal upwelling. Although survival of massive species was lower, developing a multi-species approach is key to enhance restoration success.